Remarks on derivations on semiprime rings - Mohamad Nagy Daif; Howard E. Bell (International Journal of Mathematics and Mathematical Sciences)
We prove that a semiprime ring R must be commutative if it admits a derivation d such that (i) xy+d(xy)=yx+d(yx) for all x, y in R, or (ii) xy−d(xy)=yx−d(yx) for all x, y in R. In the event that R is prime, (i) or (ii) need only be assumed for all x, y in some nonzero ideal of R.